Alternatives to Replace the Use of Zinc Oxide in Nursery Pig Diets - F. Laskoski; M. D. Tokach; J. C. Woodworth; R. D. Goodband; S. S. Dritz; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 300 pigs (DNA; 241 × 600; initially 10.6 lb) were used to evaluate the effects of different nutritional strategies to replace zinc oxide (ZnO) in nursery diets. At weaning, 5 pigs were allotted to each pen and pens were assigned to 1 of 6 dietary treatments in a completely randomized design. There were 10 replicate pens per treatment. Treatments consisted of A) Positive control (ZnO providing 3,000 ppm Zn from d 0 to 7, and 2,000 ppm Zn from d 7 to 25); B) Negative control (NC; no ZnO); C) NC plus 1.2% Na diformate; D) NC with 4% coarse ground wheat bran; E) NC with low crude protein (18%) by adding high levels of feed grade amino acids; and F) the combi- nation of NC with 18% crude protein (CP), 1.2% Na diformate, and 4% coarse ground wheat bran. Pigs were weighed on d 7, 14, 25, 37, and 46 to evaluate body weight (BW), average daily gain (ADG), average daily feed intake (ADFI), and feed-to-gain ratio (F/G). Fecal dry matter (DM) was obtained by collecting feces on days 7, 14, 25, and 37 from 3 pigs per pen. Fecal scores were assessed daily for the entire trial. From d 0 to 7, no differences (P>0.05) in any response variables were detected between treatments. From d 7 to 25, pigs fed the diet containing ZnO had greater (P<0.05) ADG and ADFI than those fed all other treatments with pigs fed the 18% CP diet having the lowest (P<0.05) ADG. Pigs fed ZnO had improved (P<0.05) F/G compared with the treatments containing 18% CP with other treatments intermediate. From d 25 to 46, when pigs were fed a common diet (no ZnO), pigs previously fed the diets containing ZnO or those that were fed the combination of NC with 18% CP, 1.2% Na diformate, and 4% coarse ground wheat bran had greater (P<0.05) ADG than pigs previously fed the NC with 18% CP with the response driven by ADFI. Overall (d 0 to 46), pigs fed diets with ZnO from d 0 to 25 had greater ADG (P<0.01), ADFI (P<0.02), and final BW (P<0.04) than those fed the NC with 18% CP which was the lowest (P<0.05) with pigs fed the other treatment diets intermediate. Pigs fed the NC diet without ZnO had the lowest (P<0.05) fecal DM and highest (P<0.05) fecal scores. Pigs fed diets with ZnO had similar fecal DM and scores as pigs fed the diet containing Na diformate, wheat bran, and 18% CP, but greater (P= 0.02) fecal DM than pigs fed singular strategies of Na diformate, wheat bran, or 18% CP. This study suggests that diets without ZnO reduce nursery performance, and lowering dietary CP and amino acids exacerbate this response. Combining the three alternatives tested (wheat bran, Na diformate, and low CP) as a replacement to ZnO improved fecal DM content and fecal score but did not result in improved performance.
Keywords: growth performance; nursery diets; zinc oxide